STUDENTS’ PERCEPTION ON THE USE OF PODCAST IN TEACHING LISTENING - Rahmiyati Rahmiyati; Merry Prima Dewi; Eliza Eliza (Universitas Mahaputra Muhammad Yamin, 2021)
This research was to find out the students' perception of the use of podcasts in teaching listening. The research was due to problems found in the field; some of the students were not interested in listening, students have difficulty catching the speakers' ideas, the perception of students toward podcast is different. The design of this research was descriptive research with a quantitative approach as the method of the research. The sample was collected from 26 students at SMK Pembangunan Bukittinggi which used total sampling as the sampling technique of the research. The result revealed the mean score of students' perception of the use of podcasts in teaching listening was 63.06%. It showed that the students had a positive perception regarding the use of podcasts in teaching listening.